Features of Sheriff Court in Scotland in Early 19th Century (Exemplified by Selkirkshire County) - S. N. Gavrilov; M. A. Mukhin (Научный диалог)
The article analyzes documents related to the sheriff court in Selkirkshire from 1799 to 1832. It investigates the extent to which legal proceedings were based on legal mechanisms. It is noted that although court materials were not meticulously filled out by the sheriff, Walter Scott, he aimed to adhere to the legal “spirit.” It is pointed out that the sheriff did not exceed the bounds of judicial jurisdiction. The punishments handed down by Walter Scott did not violate legal rules. There is no evidence that the sheriff sought to strengthen his judicial authority. It is suggested that Walter Scott did not use judicial power to cater to the most influential individuals in Selkirkshire, even though he became sheriff at their behest. In the published documents, the most authoritative figures (the third Duke of Buccleuch, the fourth Duke of Buccleuch, the fifth Duke of Buccleuch) are rarely mentioned, and legal cases only involved them in isolated instances. It is revealed that in the early 19th century, there were few individuals with legal education in Selkirkshire. Society did not demand thorough documentation from local judicial institutions, did not train an adequate number of qualified lawyers, and only marginally encouraged its representatives to formalize contracts, while providing the sheriff with insufficient salary.